Materialism and secularism in Swahili literature: The case of Topan’s Aliyeonja Pepo - Gaudioso, Roberto; Minerba, Emilio (AAeO - Afrikanistik-Aegyptologie-Online, 2020)
Concepts like materialism and secular thought have formed the basis of literary works of some of the most important authors of modern literature, such as Kezilahabi, Hussein, Mulokozi, and Topan. The value of such concepts has not always been admitted by critics: all these authors, in fact, have faced various difficulties related to their works, from open refusal (in Kezilahabi’s case) to a reluctant acceptance that neglected their critical points (in Topan’s and Hussein’s cases). The aim of this paper is to show to what extent secularism, materialism, and laicism are fundamental to these writers by selecting one case study, that of Topan’s comedy Aliyeonja Pepo,and exploring its critique of religion, both independentlyand in comparison with the other aforementioned authors. Recognizing the presence of these concepts, in fact, would allow for a deeper analysis of the internal structures of these texts and mark an advance in their critical studies.